RESULT OF TEST OF SWEET MAIZE HYBRIDS IN CONDITIONS OF SOUTH ZONE OF THE AMUR REGION - O. A. Kosicina (Овощи России, 2015)
Based on the complex of agronomical traits, the foreign sweet maize hybrids Testy Sweet, Honey, Bentham, Trophy, Sweet Nugget, and Super Sundance are recommended for growing in the conditions of the south zone of the Amur region. In this conditions, the vegetation season is 78-80 days, the yield of corn of milky ripeness is 16,9 t/ha.